ANALYSIS OF CORPORATE FINANCIAL STRATEGY OF JOINT STOCK COMPANIES AND THEIR FINANCIAL STATE - Abdulazizov Shukhratjon Botirjon ogli (Galaxy International Interdisciplinary Research Journal, 2023)
The main goal of this article is to develop a scientific proposal and practical recommendations regarding the importance of corporate financial strategy in ensuring the financial stability and growth of joint-stock companies. Financial strategies of several joint-stock companies in order to cover such goals as maintaining financial stability, increasing labor productivity, increasing production and export indicators, achieving energy efficiency, modernizing production, and achieving an increase in share value by implementing technical and technological re-equipment. analysis was carried out.